THE RECOVERY OF THE ASSETS OF THE CRIMINAL ACTS OF CORRUPTION AS THE COUNTRYS FINANCIAL RESCUE EFFORTS - Wibawa, Arif; Saidi, Djafar; Sampurno, Slamet; Arie, Martehen (Journal of Humanity, 2015)
Prosecutors in the country so that financial losses return refund losses the State has not been fullest. And existing legal institution in its implementation shows the result of maximum effort yet to refund the financial loss to the State. Therefore needs to be examined further the efforts of the Prosecutors Office has done in the optimisation of returns on the countrys financial losses.The Attorney law enforcement institutions in the framework of the financial rescue is expected to give a significant impact, so step harmonization of legislation is required to seek the repayment of assets results of criminal acts of corruption